Implementation of Brand Equity for Disaster Management Preparedness in Bengkulu - Adhrianti, Lisa (UPT Publikasi Ilmiah UNISBA, 2024)
Bengkulu Province is a disaster-prone area in Indonesia, frequently experiencing floods, landslides, earthquakes, and tsunamis. The flooding in Bengkulu City is primarily caused by coal mining activities in the upstream areas of the Bengkulu River, combined with extreme weather conditions. Effective disaster management in such regions requires not only logistical, health, and accommodation support but also robust information systems for efficient communication. This study aims to evaluate the implementation of brand equity principles by the Regional Disaster Management Agency in Indonesia, known as Badan Penanggulangan Bencana Daerah (BPBD), in Bengkulu City to enhance disaster management effectiveness. The research adopts a qualitative method, utilizing case studies and in-depth interviews with key BPBD officials. The analysis focuses on seven indicators of brand equity: leadership, stability, market, internationality, trends, support, and protection. Findings reveal that while BPBD demonstrates strong leadership and market presence, it faces challenges in achieving stability and consistent community engagement. Additionally, BPBD has successfully established international collaborations and maintained a good public image through effective media use and ethical practices. However, promotional activities are not consistently executed, and there is a need for better budget management to support disaster mitigation infrastructure. The study concludes that strengthening brand equity in disaster management agencies can significantly improve their operational efficiency and public trust, ultimately reducing disaster impact and enhancing community resilience.